Effects of probiotic and magnesium co-supplementation on mood, cognition, intestinal barrier function and inflammation in individuals with obesity and depressed mood: A randomized, double-blind placebo-controlled clinical trial - Sepideh Mahboobi; Marzieh Ghasvarian; Haleh Ghaem; Hamzeh Alipour; Shohreh Alipour; Mohammad Hassan Eftekhari (Frontiers in Nutrition, 2022)
BackgroundThe co-occurrence of obesity and mood impairments named as “metabolic mood syndrome” (MMS) is often neglected in the obesity management. This study aimed to evaluate effects of Probio-Tec ®BG-VCap-6.5 and magnesium co-supplementation on mood, cognition, intestinal barrier function and serum C reactive protein (CRP) levels in participants with obesity and depressed mood.DesignSeventy-four eligible participants were randomly allocated to either Probio-Tec®BG-VCap-6.5 [containing Lactobacillus rhamnosus (LGG®) and Bifidobacterium animalis subsp. Lactis (BB-12®)] + Magnesium chloride or placebo for 9 weeks. Sociodemographic data were collected in the beginning. Anthropometric, dietary and physical activity (PA) assessments were carried out. Beck Depression Inventory-II (BDI-II) and Montreal Cognitive Assessment (MoCA) scores were assessed through validated questionnaires. Fasting plasma zonulin, lipopolysaccharide (LPS) and (CRP) were measured by ELIZA kits.ResultsOf seventy-four participants (mean age 37.51 ± 8.10), 52 completed the study. Changes in serum LPS and zonulin were not different significantly between groups (−3.04 ± 44.75 ng/dl, 0.11 ± 5.13, ng/dl, p > 0.05 for LPS and 1.40 ± 48.78 ng/dl, −0.17 ± 6.60, p > 0.05 for zonulin, respectively). CRP levels reduced significantly in intervention group compared to placebo [−474.75 (−1,300.00, −125.00) mg/l vs. 175.20 (−957.75, 1,683.25) mg/l, p = 0.016]. Changes in BDI-II and MoCA scores were not significantly different between intervention (−7.13 ± 5.67, 1.20 ± 2.16, respectively) and placebo (−5.42 ± 6.71, 1.94 ± 1.86, respectively) groups (p > 0.05).ConclusionNine weeks of probiotic and magnesium co-supplementation resulted in decreased CRP levels as an indicator of inflammatory state with no significant effects on mood, cognition and intestinal integrity in individuals with obesity and depressed mood.